PENGARUH PELAYANAN APARAT PAJAK, MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN DAN SANKSI PAJAK TERHADAP MOTIVASI WAJIB PAJAK ORANG PRIBADI DALAM MEMBAYAR PAJAK PENGHASILAN - Meiliyah Ariani; Tyas Erasar Utami2 (Universitas Mercu Buana, 2016)
ABSTRACT This study aims to determine The Effect of The Services Tax Authorities, Tax Administration System Modernization and Tax Penalties on the Motivation of Individual Taxpayer in Paying Income Tax (Empirical Study KPP Pratama Jakarta pesanggrahan). The research data obtained from the questionnaire (primary). Model analysis of the data used in this study is the multiple linear regression analysis. Sampling was done by the method of accidental sampling method (Convenience Sampling). Based on the results of data analysis using SPSS 21 shows that the results of t-test hypothesis proves that the service tax authorities, modernization of the tax administration system and tax penalties had positive effect on motivation of individual taxpayers in paying income tax in the KPP Pratama Jakarta Pesanggrahan. The results of f-test hypothesis proves that the service tax authorities, the modernization of the tax administration system and tax penalties had positive effect on the motivation of individual taxpayers in paying income tax in the KPP Pratama Jakarta Pesanggrahan. Keywords: The Services Tax Authorities, Tax Administration System Modernization, Tax Penalties, The Motivation of Individual Taxpayer.